contribution a l'etude de dispositif PV-UPQC dans l'amelioration de la qualite de l'energie elctrique - bousnoubra choayb (My University, 2025)
Abstract This thesis explores the integration of photovoltaic (PV) systems with Unified Power Quality Conditioners (UPQC) to improve the quality of electrical energy in the context of growing energy demand and increased integration of renewable energy sources. Power quality disturbances, such as harmonics, voltage sags, swells, and imbalances, pose increasing challenges for electrical networks. Although UPQCs effectively mitigate these disturbances, their performance is optimized when coupled with PV systems. A comprehensive literature review was conducted to analyze existing technologies, followed by the development of simulation models and control algorithms aimed at regulating renewable energy production and ensuring the quality of the energy injected into the grid. Simulation results demonstrate that the proposed PV-UPQC system significantly enhances power quality while optimizing the use of solar energy. This approach contributes to a more robust integration of renewable energy sources, ensuring a stable power supply that complies with international standards. Keywords: Photovoltaic systems (PV), Unified Power Quality Conditioner (UPQC); Power quality, harmonics, voltage sags, Voltage swell, imbalances
Résumé Cette thèse explore l’intégration des systèmes photovoltaïques (PV) avec des compensateurs de puissance universels (UPQC) afin d’améliorer la qualité de l’énergie électrique dans un contexte de croissance de la demande énergétique et d’intégration accrue des énergies renouvelables. Les perturbations de la qualité de l’énergie, telles que les harmoniques, les creux de tension, les surtensions et les déséquilibres, représentent des défis croissants pour les réseaux électriques. Bien que les UPQC atténuent efficacement ces perturbations, leur performance est optimisée lorsqu’ils sont couplés à des systèmes PV. Une revue de la littérature a été réalisée pour analyser les technologies existantes, suivie du développement de modèles de simulation et d’algorithmes de contrôle visant à réguler la production d’énergie renouvelable et à garantir la qualité de l’énergie injectée. Les résultats de simulations démontrent que le dispositif PV-UPQC améliore significativement la qualité de l’énergie tout en optimisant l’exploitation de l’énergie solaire. Cette approche contribue à une intégration plus robuste des énergies renouvelables, assurant une fourniture d’énergie stable et conforme aux normes internationales. Mots-clés : Systèmes photovoltaïques (PV), filtrage universel (UPQC) ; Qualité de l’énergie électrique, harmoniques, creux de tension, surtensions, déséquilibres
Keywords: Keywords: Photovoltaic systems (PV); Unified Power Quality Conditioner (UPQC); Power quality; harmonics; voltage sags; Voltage swell; imbalances; الكلمات المفتاحية الأنظمة الكهروضوئية (PV)،المعوض الشامل لجودة الطاقة (UPQC)جودة الطاقة، التوافقيات، انخفاضات الجهد، ارتفاعات الجهد، عدم التوازن; Mots-clés : Systèmes photovoltaïques (PV); filtrage universel (UPQC); Qualité de l’énergie électrique; harmoniques; creux de tension; surtensions; déséquilibres